On S??(?,A,F)?Convergence and Strong N??(?,A,F)?Convergence - Kandemir, Hacer Şengül; Et, Mikail; Çakallı, Hüseyin (Boletim da Sociedade Paranaense de Matematica, 2023)
In this paper, we introduce strong N??(?, A, F)?convergence and S??(?, A, F)?convergence with respect to a sequence of modulus functions and give some connections between strongly N??(?, A, F)?convergent sequences and S??(?, A, F)?convergent sequences for 0 < ? ? ? ? 1. © 2023 Boletim da Sociedade Paranaense de Matematica. All rights reserved.
Keywords: A?statistical convergence; lacunary sequence; modulus function